PENERAPAN GAMIFIKASI DALAM PEMBELAJARAN BAHASA INGGRIS, PENGALAMAN BELAJAR MAHASISWA YARSI - Mahendra Bimasakti; Zulfitria Zulfitria (Taksasila Edukasi Insani, 2026)
This study aims to explore and describe students’ learning experiences through the implementation of gamification in English learning at YARSI University Jakarta, with a particular focus on speaking activities. The study addresses the need to enhance student engagement in English classes amid academic demands that often reduce active participation. A qualitative case study approach was employed, and data were collected through classroom observation, in-depth interviews, and focus group discussions. The findings show that gamification, implemented through daily missions, group-based competition, and point-based classroom activities, increased students’ active participation in speaking practice. It also encouraged learning engagement both inside and outside the classroom, fostered collaboration among students, enhanced self-confidence, and reduced anxiety in using English. However, the study also identified several challenges, including students’ academic workload, technical constraints in completing gamified tasks, and perceptions of unfairness in some competitive activities. Overall, the study concludes that gamification is an effective strategy for creating more meaningful and engaging English learning experiences in higher education.Keywords : gamification, learning experience, speaking skill, university students, YARSI University